Robust, scalable construction of an electrophilic deuterated methylthiolating reagent: facile access to SCD3-containing scaffolds - Xiao, Xiao; Huang, Yin-Qiu; Tian, Hong-Yu; Bai, Jun; Cheng, Fei; Wang, Xu; Ke, Miao-Lin; Chen, Fen-Er (Chemical communications (Cambridge, England), 2022)
We have established a practical and concise method for the straightforward access of a universal deuterated methylthiolating reagent through a one-pot gram-scale operation under mild conditions. This odourless electrophilic SCD3 reagent was widely applied to react with numerous representative nucleophiles and approached various valuable SCD3 analogues with excellent levels of deuterium content (>99% D). The divergent further transformations were smoothly carried out to obtain the significant derivatives with different oxidative states in high efficiency.